Proceedings of the 25th ACM SIGSPATIAL International Conference on Advances in Geographic Information Systems 2017
DOI: 10.1145/3139958.3139992
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Driving Context from Driver Behavior

Abstract: Because of the increasing availability of spatiotemporal data, a variety of data-analytic applications have become possible. Characterizing driving context, where context may be thought of as a combination of location and time, is a new challenging application. An example of such a characterization is finding the correlation between driving behavior and traffic conditions. This contextual information enables analysts to validate observation-based hypotheses about the driving of an individual. In this paper, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Apart from harnessing videos and crowd-sourced information, several works [14], [15] are done on abnormal driving behavior detection by exploiting IMU and GPS data. To prevent fatal accidents, authors [16]- [18] try to alert the drivers whenever risky driving signature is observed, such as lane departure or sudden slow-down indicating congestion. However, they have not looked into the effect of neighboring vehicles or other surrounding factors on various driving maneuvers.…”
Section: Related Workmentioning
confidence: 99%
“…Apart from harnessing videos and crowd-sourced information, several works [14], [15] are done on abnormal driving behavior detection by exploiting IMU and GPS data. To prevent fatal accidents, authors [16]- [18] try to alert the drivers whenever risky driving signature is observed, such as lane departure or sudden slow-down indicating congestion. However, they have not looked into the effect of neighboring vehicles or other surrounding factors on various driving maneuvers.…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, we set the minimum duration of a trajectory to be 10 minutes and the maximum to 30 minutes. This step will not limit the generalizability of our method, but ensures to have enough data for each trajectory and helps to achieve reasonable running time by avoiding long trajectories 3 . Lastly, we remove those trajectories with any missing attribute to preserve consistency in data.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…The problem of learning driving style is specifically important for driver risk prediction used by insurance companies * All rights reserved to the authors, and The Ohio State University (2021). [1][2][3]. The shift towards more personalized insurance products has created a need for understanding driving style at an individual level.…”
Section: Introductionmentioning
confidence: 99%
“…• ψ 3 : End the current segment after a drastic change in the signal, where the drift is captured using signal segmentation approaches. We employ the Wedding Cake technique for the dynamic segmentation of our signals [30,31].…”
Section: Principlesmentioning
confidence: 99%